2021
DOI: 10.3390/agronomy11081488
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control Efficacy and Crop-Weed Selectivity of a New Bioherbicide WeedLock

Abstract: Plant-based bioherbicides could be an effective alternative to current chemical herbicides for sustainable agriculture. Therefore, this research evaluated the weed control efficacy and crop-weed selectivity of the new plant-derived bioherbicide WeedLock compared to commercial herbicides in glasshouse and field conditions. In the glasshouse, the herbicides applied were WeedLock (672.75, 1345.50, 2691.00 L ha−1), glyphosate isopropyl-amine, and glufosinate-ammonium (1, 2, 4 L ha−1), over the untreated (control) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Furthermore, the youngest generations need to be alert to the climate's effect on weeds from time-to-time. The new weeds will compete with the existing plants and cooperation is required between farm managers, researchers, and local people to improve the weed problem [108,109].…”
Section: Climate Changementioning
confidence: 99%
“…Furthermore, the youngest generations need to be alert to the climate's effect on weeds from time-to-time. The new weeds will compete with the existing plants and cooperation is required between farm managers, researchers, and local people to improve the weed problem [108,109].…”
Section: Climate Changementioning
confidence: 99%
“…Concerns over these issues have prompted the interest in exploring alternative weed management strategies using natural products for better sustainability 37 , 38 . Our previous work has demonstrated that WeedLock is a promising novel bioherbicide with an excellent weed control efficacy under both glasshouse and field conditions 39 . In this study, the physiological and biochemical changes in A. conyzoides , E. indica , Z. mays , and A. gangeticus following WeedLock exposure at different time points were investigated as a continuation to our previous work.…”
Section: Discussionmentioning
confidence: 99%
“…The “Marrone BioInnovations” company tested >12,000 microorganisms and prepared three BCHs for registration [ 168 ]. It has been reported that more than ten formulations based on plant extracts and essential oils were tested, but they have not been widely used [ 116 , 169 ]. The experimental BCH formulation containing tenuazonic acid as AI was successfully evaluated in the field against the main weeds of cotton and tobacco [ 170 ].…”
Section: Perspectives Of Natural Compounds As Biorational Herbicidesmentioning
confidence: 99%